Scientific Approach Improves Yield and Quality of Apples: A Success Story of Kotkhai in Shimla District of Himachal Pradesh, India - Sharma, N. C.; Kaith, N. S. (International Journal of Economic Plants, 2015)
Amongst the cash fruit crops, apple is leading in Himachal Pradesh. However, the productivity of the apple crop is very low and quality of the produce is also not up to the mark due to dependency on old Delicious standard varieties and non-scientific approaches of orchard operations. The present success story is a case study of a progressive apple orchardist who has not only diversified his apple production by introducing new spur varieties but also increased the production and improved the quality of his produce by adopting scientific approaches for orchard operations. The orchardist was a Navy officer till 2004 and his family was cultivating apples with traditional non-scientific techniques and facing many problems like poor fruit set, low production, poor fruit quality, biennial bearing and low returns but after his involvement in the family enterprise in 2005, the production and income of enterprise has increased many folds. Today, he is harvesting fruits of Super chief, Ace spur, Scarlet Spur I and II, Schlect Spur Delicious and Gale Gala varieties and a proud orchardist with a productivity of 16.0 tons acre-1 and an annual income of about INR18 lacs acre-1.